Gas chromatography and mass spectrometry : a practical guide - Sparkman, O. David [ (Orrin David)] , 1942-; Kitson, Fulton G.; Penton, Zelda E. (Elsevier/Academic Press, 2011)
The second edition of Gas Chromatography and Mass Spectrometry serves as an indispensible resource for those learning and practicing GC/MS. While retaining the original goals of brevity and accessibility, the authors have expanded the science and techniques to include those that have emerged since the publication of the previous edition. Throughout the book, quick references to data interpretation facilitate the extraction of information from GC/MS data